Baseline-Endline Report: Reaching the Unreached (RtU) through Open and Distance Learning (ODL) in Bangladesh, India and Pakistan - Ferreira, Frances; Cruz, Charisse; Smith, Kristina; Commonwealth of Learning (COL) (British Columbia) (Commonwealth of Learning, 2018)
This report documents the baseline-endline study by the GIRLS Inspire team's Reaching the Unreached project to examine the implications of skills training and education for women's and girls' empowerment and sustainable livelihoods in Bangladesh, India and Pakistan. It is based on data collected from quarterly reports mirrored against the project outcomes, meeting reports and surveys from March 2016 to March 2017. The quarterly and meeting reports documented the activities undertaken to provide training for unreached women and girls in the selected countries. While the actual training was offered exclusively to women and girls, the reports and surveys also captured the input of men and boys in terms of their participation in various community events and as staff members of the partner organisations.
KerkoCite.ItemAlsoKnownAs: 2339240:6XL37978 2405685:NM8GPWDQ
Keywords: Access to Education; Bangladesh; Barriers; Child Abuse; Decision Making; Distance Education; Dropouts; Economic Factors; Educational Attainment; Elementary Secondary Education; Employer Attitudes; Employment; Empowerment; Females; Foreign Countries; Health; Income; India; Job Skills; Marriage; Occupational Aspiration; Pakistan; Postsecondary Education; Program Effectiveness; Skill Development; Sustainability; Training; Womens Education